Modern forms of iodine-containing food components - A. S. Dydykin; Yu. N. Zubarev; E. I. Logunova; Yu. A. Kuzlyakina (Теория и практика переработки мяса)
The article presents the statistics of iodine deficiency disorders and the possible causes of their occurrence. The methods of iodine deficiency correction on the basis of state programs are reviewed. The recommendations from the World Health Organization on the amount of iodine added to iodized salt are given. A review of scientific databases on the topic of iodine-containing food components of various nature and their classification are given based on the form of the components (organic or inorganic). The analysis of iodine preservation in foods incorporating iodine-containing components under various conditions of technological processing and storage has been carried out.